2013
DOI: 10.4238/2013.july.30.8
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms in immunity-related genes and their association with mastitis in Chilean dairy cattle

Abstract: ABSTRACT. Mastitis remains a major cattle disease with great global economic implications. Various approaches are currently employed in attempts to improve understanding of mastitis resistance and develop phenotypic markers for use in breeding programs (e.g., somatic cell score), including QTL discovery, wide-genome association studies, and identification of candidate genes related to immune function. This study evaluated three single nucleotide polymorphisms contained in Toll-like receptor 4 (TLR4) and lactof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 41 publications
(49 reference statements)
2
10
0
Order By: Relevance
“…Numerous studies have demonstrated a potential role for TLR2 and TLR4 in the development of mastitis in dairy cattle [10], resistance to bacteria [11], and ability to affect the level of bacteria in milk [12]. Both LPS and LTA are able to cause an inflammatory response via TLR signaling [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated a potential role for TLR2 and TLR4 in the development of mastitis in dairy cattle [10], resistance to bacteria [11], and ability to affect the level of bacteria in milk [12]. Both LPS and LTA are able to cause an inflammatory response via TLR signaling [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…In our research, the most frequent variant found at this locus was allele C (62 %). Similarly, Carvajal et al (2013) found allele C as the predominant variant in Chilean dairy cattle. However, in a Canadian Holstein, the predominant allele was G (60 %) (Sharma et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The G allele was associated with increased protein con tent in milk, and allele delCCT was associated with in creased milk yield and fat content [56] H3 haplotype (G 1 C 2 G 3 T 4 C 5 C 6 T 7 ) was associated with reduced levels of saturated fatty acids and lau ric acid (C12:0) and high concentration of unsatur ated and monounsaturated fatty acids as compared to haplotype H1 (G 1 C 2 C 3 C 4 A 5 C 6 A 7 ) during first 3 months of lactation Associated with the percentage of fat and protein in milk at 141-305 days of lactation [69] TT genotype is associated with resistance to mastitis [86] Transition protein 2 (TNP2) g.269G>A (exon 1), g.480C>T (intron 1), g.1536C>T (3' UTR)…”
Section: A>g 17266indelcctmentioning
confidence: 99%